PEREMPUAN DALAM KELUARGA MENURUT KONSEP ISLAM DAN BARAT - Warsito, Warsito (Muhammadiyah University Press, 2013)
Islam as ideology is agent of change. When it came to the Arabic people, theconditions of women were so pity. They never got their rights of human being but sometribes killed the daughter baby. After it came to the world, women got their duties, theywere allowed to make transaction and their right life is saved. Islam is a religion whichrules all field of human being life side. It rules the roles of man and woman and theirduties. Not only ruling the roles and duties but also the way how to practice the religion.Nowadays, feminists make confrontation ideas. They said that Islam is injustice religion.They said that women are better to pray at home and men pray at the mosques. Theydisagree that leader is only for men but they see that it is also womenâs right. Theyargued that women today are so different from the past. The feministsâ idea that supportsme to conduct the study. The aims of this study is to compare the Islamic teaching andfeministsâ teaching by using Maqasid Syariâah. The result of the study is, Islamicteachings are appropriate rules for human being but feministsâ teaching damage thesocial norms and womenâs right.Key words: women, family, Islam, westSebagai sebuah ideologi, Islam merupakan agen perubahan. Ketika Islamdatang kepada orang-orang Arab, kondisi perempuan sungguh mengenaskan.Kaumperempuan tidak pernah mendapat hak-hak mereka sebagai manusia, bahkan beberapasuku membunuh bayi perempuan yang baru lahir. Dalam perkembangannya, wanitapunya tugas-tugas dan diizinkan untuk berperan dalam masyarakat serta memperolehhak-haknya. Islam adalah agama yang mengatur semua bidang kehidupan manusia.Termasuk dalam mengatur peran dan tugas-tugas kaum laki-laki dan perempuan. Tidakhanya mengatur peran dan tugas tetapi juga bagaimana cara mempraktekkan ajaranagama dalam kehidupan sehari-hari. Saat ini, feminis mengusung ide-ide yangbertentangan dengan Islam, antara lainmereka mengatakan bahwa Islam adalah agamayang mengajarkan ketidakadilan, Islam membedakankesempatan wanita lebih baik untukberibadah di rumah dan laki-laki beribadah di masjid-masjid. Makalah ini berusahamembandingkan ajaran Islam dan ajaran feminis dalam masalah peran perempuandalam keluarga dengan menggunakan Maqasid Syariâah. Hasil dari penelitian ini adalah,ajaran Islam adalah aturan yang sesuai untuk manusia tetapi ajaran feminiscenderungmengabaikan norma-norma sosial dan hak perempuan.Kata kunci: perempuan, keluarga, Islam, barat